The implementation of attitude assessment in Curriculum 2013 at elementary schools - Ulumudin, Ikhya; Fujianita, Sisca (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
This study is aimed at describing the implementation of attitude assessment conducted by teachers starting from the assessment planning, implementation, results processing, its utilization, and the follow-up. This study employed a qualitative and quantitative method. The subject was elementary school teachers in Bekasi city who had taught in classes applying Curriculum 2013. The data were collected using questionnaires and focus group discussions. The result shows that the implementation of attitude assessment had not been done optimally because of teachers' lack of understanding. Besides, too many techniques of attitude assessment cause teachers to need a lot of time to learn and conduct the assessment. In Curriculum 2013, students' involvement is emphasized, yet most students were quite passive in class, and there was no dynamic and active discussion in the learning process. It means teachers need to apply different methods to encourage students to be more active. Lastly, the utilization and follow-up of the assessment results were not optimal. Some recommendations that can be proposed are: (1) schools are hoped to be able to provide independent training for the implementation of assessment in Curriculum 2013; (2) mandatory attitude assessment required to be done by each subject teacher is observation, while other required assessments are done by the classroom teacher; (3) variables in attitude assessment needs to be completed and clearly stated especially in social aspects (KI-2), which are accepting and responding; (4) there should be a detailed description of attitude assessment in students' reports.